Relationship between functional capacity and socioeconomic status in a cohort of Turkish heart failure patients - Hakkı Kaya; Meltem Refiker Ege; Ali Zorlu; Osman Beton; Hasan Güngör; Ahmet Temizhan; Yeşim Güray; Yüksel Çavuşoğlu; Mehdi Zoghi; Mehmet Birhan Yılmaz; On Behalf Of TREAT-HF Investigators (KARE Publishing, 2016)
Objective: New York Heart Association (NYHA) classification predicts prognosis for heart failure (HF) patients. Socioeconomic status (SES) has the potential to affect treatment strategy and disease course. The present objective was to investigate whether SES of Turkish HF patients affected NYHA classification. Methods: Turkish research team-HF (TREAT-HF) is a questionnaire study with 52 questions, the purpose of which is to aid in the assessment of various qualities of HF patients. The 2013 TREAT-HF cohort included 503 patients from 11 centers in Turkey. Patients were divided into 2 groups according to NYHA functional classification: I-II, a better functional classification, or III-IV, a poorer functional classification. In addition, patients were analyzed according to gender. Results: Evaluated were NYHA functional classifications of 459 (326 males and 133 females) patients with a mean age of 59.7+-14.07 years and a mean ejection fraction (EF) of 31.7+-9.22%. Total monthly family income level of ≥1000 TL, younger age, higher EF, and male gender were independently associated with better NYHA functional classification. In addition to EF, regular weight control was found to be independently associated with better NYHA classification for females, while younger age and income of ≥1000 TL were independently associated with better NYHA classification for males. Conclusion: The present results demonstrated that SES was associated with NYHA functional classification in a cohort of Turkish HF patients.